Why continuous improvement initiatives fail in manufacturing environments? A systematic review of the evidence. Issue 3 (8th April 2014) - McLean, Richard; Antony, Jiju
Abstract : Purpose: – The purpose of this paper is to present the core themes derived from literature that contribute to the failure of continuous improvement initiatives in the manufacturing industry. Design/methodology/approach: – The approach taken was to complete a systematic review of literature, grouping the failure factors through the use of idea maps and affinity diagrams into the core themes reported. Findings: – From the review it is evident that continuous improvement initiatives can fail due to a multitude of factors; but that these can be grouped under eight core themes. The themes found to contribute to the failure of continuous improvement initiatives are: Motives and Expectations, Organizational Culture and Environment, The Management Leadership, Implementation Approach, Training, Project Management, Employee Involvement Levels, and Feedback and Results. These themes have been further categorized into a three-stage model. Research limitations/implications: – The review was carried out using a selection of high-quality journals, although this may have restricted the findings. The research is also limited to manufacturing, so it is unknown if the same factors impact initiatives in the service or public sectors. Continuous improvement is defined for the purpose of the study as TQM, Lean, and Six Sigma. Originality/value: – From a practical perspective, the research findings create awareness for organizations of the complexity of organizational change in the form of continuous improvement implementation.